The Impact of Corporate Governance Practices on Audit Quality in Malaysian Public Listed Companies - Ho, Wai Kee (2016)
Audit committees are tasked to protect investor interests by taking the lead on oversight responsibilities in audit activities, particularly to preserve audit quality. Its main role is governed by regulatory requirements of the relevant authorities within the regional and corporate governance codes. This thesis examines the influence of corporate governance practices on audit quality in Malaysian Public Listed Companies. Audit committee effectiveness is used as a proxy of corporate governance practices and audit fee and non-audit service fee are used as proxies of audit quality. 457 listed companies are selected as the sample of the study. Data was obtained from annual reports of companies filed with Bursa Malaysia Resource Center. Pooled ordinary least square regression analysis is used to predict the audit fee and non-audit service fee based on effectiveness of audit committees, factors that related to board of directors and company related factors to explore various relationships between best practices of corporate governance and audit quality. The research results show that all hypotheses have not been supported, suggesting that the effectiveness of audit committee has no significant impact on audit quality. The outcome, targeting the regulators to improve the quality of corporate governance, suggests a scrutiny of existing audit mechanism and focus area of audit function to ensure that gaps in the audit processes are bridged between the audit committee and the audit quality. The recommended actions for future research is to look at the relationship between audit committee and its terms of reference which possibly can be a limitation parameter that affects the efficacy of corporate governance quality.